New forms of employment and new problems of regulation - Regalia, Ida (Regulating New Forms of Employment, 2006)
This book deals with forms of employment other from the one that became dominant in the most developed twentieth-century economies following the advent of standardized mass production. I refer to those types of employment variously termed 'atypical', 'contingent', 'precarious', 'new', 'non-standard', 'non-traditional', 'ﬂexible' (Córdova 1986; Rodgers and Rodgers 1989; Delsen 1995; Summers 1997; Kalleberg 1999) and which constitute a heterogeneous array of 'particular' (Germe and Michon 1980) ways with which employers ensure the availability of labour, and, vice versa, with which diverse groups of workers establish contractual relationships with employers/contractors. Such forms of employment are subject to relatively little regulation, or they are regulated differently with respect to the dominant form. Their spread over the last ﬁfteen to twenty years in Europe, the United States and the other developed countries signals changes which for some time have affected work, the institutions that regulate it, and its meaning itself for individuals and society.